Aneurysms of the Anterior Communicating Artery Treated with Guglielmi Detachable Coils: Follow-Up with Contrast-Enhanced MR Angiography - Leclerc, Xavier; Navez, Jean-François; Gauvrit, Jean-Yves; Lejeune, Jean-Paul; Pruvo, Jean-Pierre (American Journal of Neuroradiology, 2002)
BACKGROUND AND PURPOSE: The long-term outcome of patients treated with Guglielmi detachable coils (GDCs) remains unknown and is being evaluated. We sought to assess the feasibility and utility of contrast-enhanced MR angiography in the follow-up of anterior communicating artery (AcomA) aneurysms treated with GDCs.METHODS: In a prospective study, 20 consecutive patients with AcomA aneurysms underwent digital subtraction angiography (DSA), time-of-flight MR angiography (TOF-MRA), and contrast-enhanced MR angiography (MRA) 12 months after treatment with GDCs. The aneurysmal sac measured less than 10 mm in 19 patients and 12 mm in one patient. Two observers who did not analyze the DSA images independently reviewed the MRA images. Aneurysms were classified according to the presence of a residual neck (ie, complete occlusion, small residual neck, large residual neck, or not assessable). DSA was used as the standard of reference.RESULTS: Images from all examinations were assessable. Venous enhancement was observed in five cases at contrast-enhanced MRA; this did not affect image interpretation. Interobserver agreement was good. A comparison of the techniques showed good agreement in the detection of a residual neck. Two cases of a small residual neck were not detected at TOF-MRA, and one case of complete occlusion was misclassified as a small residual neck at contrast-enhanced MRA.CONCLUSION: Our findings showed that contrast-enhanced MRA is a valuable method for the follow-up of aneurysms in the AcomA after their treatment with GDCs. Further studies with multiple aneurysm locations and larger groups are required to determine the exact role of this technique.